2010
DOI: 10.1590/s0100-54052010000100010
|View full text |Cite
|
Sign up to set email alerts
|

Reação de cultivares de algodoeiro a Ramularia areola

Abstract: Among the disease causing leaf spot in cotton, the gray mildew (Ra mul aria areol a Atk.) has become import ant due to environmental conditions favorable for development of the disease susceptible cultivars, consecutive and intensive and extensive cultivation. This work evaluated the resistance of the cultivars Delta Opal, Acala 90, Makina, Delta Penta and Sure Grow 821 to resistance the R. areola, in field conditions in FCAV-UNESP. The disease occurred under natural infection and, its severity was evoluated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 4 publications
1
3
0
1
Order By: Relevance
“…Although [30] found similar results to the present study, in which the severity progress curves for the red rot of sisal (Agave sisalana Perrine) caused by fungus Aspergillus Niger did not fit any of the tested mathematical models, [31] found a better fit of monomolecular model for the progress curves of areolate mildew in five cotton cultivars. [32] evaluating the areolate mildew severity in different handling systems, reported less severity of disease in sowing direct system (SDS), whose principles are based in the cover soil and in the crop turn, followed of conventional system with crop turn biannual.…”
Section: Discussionsupporting
confidence: 85%
“…Although [30] found similar results to the present study, in which the severity progress curves for the red rot of sisal (Agave sisalana Perrine) caused by fungus Aspergillus Niger did not fit any of the tested mathematical models, [31] found a better fit of monomolecular model for the progress curves of areolate mildew in five cotton cultivars. [32] evaluating the areolate mildew severity in different handling systems, reported less severity of disease in sowing direct system (SDS), whose principles are based in the cover soil and in the crop turn, followed of conventional system with crop turn biannual.…”
Section: Discussionsupporting
confidence: 85%
“…In countries like Madagascar and India, yield losses due to the disease can reach up to 60 % of the crop ( Kirkpatrick & Rothrock 2001 ). In Brazil it was considered a minor disease but the expansion of the cultivated area on cotton and the introduction of susceptible varieties increased the disease incidence and yield losses now reach 30 % of crop production ( Lima et al. 2010 ).…”
Section: Resultsmentioning
confidence: 99%
“…Several authors have described the resistance and susceptibility of cotton to Ramularia leaf spot (Lima et al, 2010;Cia et al, 2008Cia et al, , 2014. In this study, were observed significant interactions between genotype and chemical fungicide and biofungicide treatments.…”
Section: Discussionmentioning
confidence: 55%